2020
DOI: 10.1007/s10980-020-01005-9
|View full text |Cite
|
Sign up to set email alerts
|

Regional variability in landscape effects on forest bird communities

Abstract: Context Functional responses to landscape heterogeneity are context-dependent, hampering the transferability of landscape-scale conservation initiatives. Japan provides a unique opportunity to test for regional modification of landscape effects due to its broad temperature gradient, coincident with a gradient of historical disturbance intensity. Objectives To quantify and understand how regional contexts modify forest bird community responses to landscape heterogeneity across Japan. Methods We characterised th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 105 publications
0
10
0
Order By: Relevance
“…We used the bird data from 2009 to 2020 because a different survey method was used at the forest and grassland sites before 2009. We took the maximum number of individuals observed for each species at each site each year from the repeated surveys following the approach of Spake et al (2020). We assumed that the abundance was generally underestimated by point or linetransect counts and, therefore, that the maximum number of birds detected in any visit represented the minimum number at that location (Spake et al, 2020).…”
Section: Bird Abundance Datamentioning
confidence: 99%
See 1 more Smart Citation
“…We used the bird data from 2009 to 2020 because a different survey method was used at the forest and grassland sites before 2009. We took the maximum number of individuals observed for each species at each site each year from the repeated surveys following the approach of Spake et al (2020). We assumed that the abundance was generally underestimated by point or linetransect counts and, therefore, that the maximum number of birds detected in any visit represented the minimum number at that location (Spake et al, 2020).…”
Section: Bird Abundance Datamentioning
confidence: 99%
“…We took the maximum number of individuals observed for each species at each site each year from the repeated surveys following the approach of Spake et al (2020). We assumed that the abundance was generally underestimated by point or linetransect counts and, therefore, that the maximum number of birds detected in any visit represented the minimum number at that location (Spake et al, 2020). We concluded that the imperfect detection of birds would not affect our findings (further discussion in Appendix S4).…”
Section: Bird Abundance Datamentioning
confidence: 99%
“…Forest plantations in the steppe exist in highly extreme conditions in the steppe, which is due to the significant variability of bird life conditions in them. Contamination, felling, fires and the disturbance factor are the reasons for sharp fluctuations in the bird population in artificial plantations (Spake et al, 2020). The precipitation factor was the leading one for forming the dynamics of bird communities in forest strips.…”
Section: Discussionmentioning
confidence: 99%
“…We collected data for each species’ five functional traits included in the analysis: body mass, dispersal ability, diet, foraging stratum, and habitat specificity. These five traits were chosen because previous studies have indicated that they are related to species abundance or range size across different scales, from local to global ( e.g ., Pigot et al, 2018 ; Valente & Betts, 2019 ; Spake et al, 2020 ). Body mass for all species was gathered from the literature ( Wilman et al, 2014 ).…”
Section: Methodsmentioning
confidence: 99%